Báo cáo Giải trình, tiếp thu, chỉnh lý dự thảo Nghị quyết Kỳ họp thứ 7, Quốc hội khóa XV - Ủy ban Thường vụ Quốc hội (2024)
Toàn văn Báo cáo Giải trình, tiếp thu, chỉnh lý dự thảo Nghị quyết Kỳ họp thứ 7, Quốc hội khóa XV.